Anxiety and Motivation to Return to Sport During the French COVID-19 Lockdown - Ruffault, Alexis; Bernier, Marjorie; Fournier, Jean; Hauw, Nicolas (Frontiers in Psychology, 2020)
Feeling anxious and presenting self-determined motivations about returning to sport after a break may impair sport performance and increase the risk of sustaining an injury. Hence, the aim of this study is to explore differences in anxiety and motivation to return to sport according to gender, expertise, training status before and during the lockdown, and athletes’ availability (i.e., injury status) at the time of the lockdown. A total of 759 competitive athletes (49% female; mean age: 27 ±10 years old) completed the cross-sectional study. Participants were invited to state their expertise, training status before and during the lockdown (did they have a training program), and whether they were injured at the start of the lockdown. Additionally, participants filled out psychometric self-report measures of anxiety (TFAI-return) and motivation (SMS-return) to return to sport. Due to non-normal distributions in the TFAI and SMS scores, non-parametric group comparisons were performed to compare participants for each categorical variable: non-parametric correlation tests were also performed to test the associations between continuous variables. Group comparisons showed higher scores of anxiety for females, younger athletes, athletes practicing and competing at the highest level, and athletes without a training program during the lockdown. Moreover, results suggested lower motivation scores (i.e. autonomous and controlled) for older athletes, experts (practicing for more than 10 years), athletes practicing and competing at a lower level, and athletes without a training program during the lockdown. Additionally, participants who were injured at the start of the lockdown reported higher scores of cognitive anxiety to return to sport than non-injured participants. The results of this study suggest that elite athletes may have suffered from external pressures to return to sport during the lockdown. Additionally, participants with a training program during the lockdown seemed to be less anxious and more self-determined to return to sport after the lockdown. Future studies may focus on the impact of cognitive behavioral interventions on anxiety and motivation to return to sport.